AVALIAÇÃO DA RELAÇÃO ENTRE A CONDUTIVIDADE HIDRÁULICA DO SOLO SATURADO COM PARÂMETROS FÍSICOS DE UM LATOSSOLO VERMELHO DISTRÓFICO SUBMETIDO A DOIS DIFERENTES MANEJOS - Ferreira, Silvana Travinski (2008)
Some soil physical properties alter due to the management conducted on them. It is the management that largely produces the main modifications in the soil structure. Soil non harvest and conventional managements are the more investigated cultivation methods. Non harvest appeared as an alternative to the conventional, nevertheless, comparative studies of the alterations produced by those two types of management systems can supply important subsidies in the analysis of the advantages and disadvantages of a system in relation to the other. The objective of this work was to compare the saturated soil hydraulic conductivity of a Red Latossol submitted to non harvest, conventional tillage and secondary forest and, to correlate it to other physical properties of the soil, such as soil particle density, soil particle distribution (sand, silte and clay), soil bulk density, soil micro and macro porosity. The saturated soil hydraulic conductivity was obtained using a Guelph permeameter. A rectangular mesh composed of 35 measurement positions was used. The investigated physical properties were analyzed using the classical statistics, which is based on the calculation of averages, standard deviation, variation coefficient, minimum and maximum values and asymmetry and curtosys coefficients. Also, there were made histograms to verify the nature of the distribution and the variability of the measured variables and boxplot graphs to identify discrepant points. For a visualization of their variability, maps of these properties were performed. As compared to the non harvest, the conventional tillage system presented a larger saturated soil hydraulic conductivity. The soil saturated hydraulic conductivity did not present correlation with no other properties of the soil than soil macroporosity, for both investigated soil tillage management.